Marxist Political Economy and the Crisis of Relevance in Contemporary World - Essia, Uwem; Okoi, Ifere Eugene (International Journal of Sustainable Development & World Policy, 2013)
This paper set out to support the Marx’s thesis that an economic system founded on exploitation and inequities is prone to crises. It agrees however that some assumptions of Marx have been faulted with passage of time, but maintains that Marxism remains relevant as long as its central message cannot be faulted. The methodology adopted was both historical and comparative. The historical approach was used to situate Marxism within the stream of dominant economic thought, and show how well it explains the various historical epochs from primitive era to the more recent post modern societies. The comparative approach was used to review the socialist governments in China and the defunct USSR. The outcome of both approaches point to the fact that Marxism needs to restructure itself to remain continually relevant. More importantly, neo-Marxists need to admit the possibility of change emanating simultaneously from both the political superstructure and the economic base, which among other things, make incorporation of Hegel’s phenomenology into mainstream Marxism expedient.